Natural enrichment of chromium and nickel in the soil surrounds the karst watershed - R.D.P. Astuti; A. Mallongi; A.U. Rauf (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: As a public concern, monitoring and controlling toxic metals pollution is needed worldwide. Due to the ability of poisonous metals in biomagnification and bioaccumulation, they can cause several adverse impacts on ecological and human health. The study aims to assess chromium and nickel enrichment levels and estimate the soil''s ecological risk surrounds the Pangkajene watershed. METHODS: The total concentrations of chromium and nickel were determined using the Flame Atomic Absorption Spectrophotometer. This study used contamination factor, geo-accumulation index, and pollution load index to evaluate soil enrichment status. The ecological hazard index is used to estimate the potential hazard that may occur due to contamination.  FINDINGS: The mean concentrations of chromium and nickel were 92.9 and 43.18 mg/kg, respectively. Chromium concentration exceeded the soil quality guideline for the protection of environment and human health, while Ni still below the standards. The geo-accumulation index value indicated no human-made-derived contamination in the soil. Weathering of carbonate rocks is the chromium and nickel major enrichment factor in the Pangkep regency. Contamination factor and pollution load index values showed low pollution in the studied soil. However, all study sites exceeded the ecological hazard index value (Ecological hazard index>1), which indicates a considerable ecological risk in the Pangkajene watershed area.  CONCLUSION: These findings may provide baseline information related to chromium and nickel enrichment in the soil for Pangkep regency municipality. The Pangkep regency municipality must highlight the importance of strengthening environmental standards and monitoring mechanism as the priority to maintain a healthy environment.